Conjugation of peptides to the passivation shell of gold nanoparticles for targeting of cell-surface receptors - Maus, Lisa; Dick, Oliver; Bading, Hilmar; Spatz, Joachim P.; Fiammengo, Roberto (ACS nano, 2010)
We report the preparation of gold nanoparticles (AuNPs) functionalized with the peptide-toxin conantokin-G and their selective binding to N-methyl-d-aspartate (NMDA) receptors recombinantly expressed by transfected HEK 293 cells. The AuNPs are passivated with a mixed self-assembled monolayer of ω-carboxy- and ω-amino-polyethylene glycol (PEG) thiols. We compare two different passivation systems: the alkyl-PEG600 system is characterized by a C11-alkyl chain between the thiol group and the PEG segment, whereas the PEG3000 system lacks this alkyl-chain. We show that only the alkyl-PEG600 passivation system allows selective conjugation of cysteine-terminated peptides to the periphery of the passivation layer via a heterobifunctional linker strategy. In contrast, using the PEG3000 passivation system, peptides are immobilized both on the passivation layer and directly on the gold surface via concurrent place-exchange reaction. We therefore recommend the use of the alkyl-PEG600 system to precisely control the number of immobilized peptides on AuNPs. In fact, we show that the number of conjugated peptides per particle can be varied with good control simply by varying the composition of the self-assembled monolayer. Finally, we demonstrate that conjugation of the conantokin-G peptide to the solvent-exposed interface of the passivation layer results in maximal binding interaction between the peptide-functionalized AuNPs and the targeted NMDA receptors on the cell surface. Conantokin G-coupled AuNP may be used to spatially restrict NMDA-receptor-blockade on neuronal surfaces.
Gesehen am 30.05.2023